Conflicts Of The Main Character In Critical Eleven Movie - Ekapratama, Febryanto; Sinaga, Lidiman Sahat Martua (Universitas Negeri Medan, 2021)
This study focuses on conflicts that were faced by Tanya Baskoro as the main character on the Critical Eleven movie, the aim of this study is to find out kinds of conflict that were faced by the main character of the movie, then to analyze the strategies used by the main character in dealing with the conflicts, and explaining the factors that lead the main character to use particular strategy in dealing with particular conflict. The study was conducted using qualitative design, where it started from identifying, classifying, tabulating, then analyzing the data, the data gotten from the statements and dialogues from the movie. Using theory from two experts it was found that the main character was faced with two types of conflicts, External and Internal Conflicts, the dominant kind of conflict occurred to the main character is Man-Against-Man conflict. The most used strategy of the main character to deal with the conflicts are Competing and Avoiding strategy.